Microplastics and heavy metals in the sediment of Songkhla Lagoon: distribution and risk assessment - Pradit, Siriporn; Noppradit, Prakrit; Sornplang, Kittiwara; Jitkaew, Preyanuch; Kobketthawin, Thawanrat; Nitirutsuwan, Thongchai; Muenhor, Dudsadee (Frontiers in Marine Science, 2024)
This study reports the occurrence of microplastics (MP) and heavy metals in the sediment of Songkhla Lagoon, the largest lagoon in Thailand. This work was conducted at the beginning of February 2023. Heavy metal and MP contamination of aquatic systems is a major environmental issue that affects human health globally. In the sediment samples taken from 10 sampling sites, fibers were found at all stations at 68.24% (15.15 items/g) and fragments were found at 31.76% (7.05 items/g). The highest number of MP particles was found at the area near the mouth of the lagoon ( 5. 4 items/ g). The average concentrations (mg/kg) of heavy metal at all sites showed the following trend: Mg (732.54±247.04) > Mn (176.74±83.68) > Zn (29.36±39.47) > Cu (12.31±24.58) > Pb (11.07±7.60) > As (5.64±3.30) > Co (2.90±1.38) > Cd (0.22±0.17). Regarding the overall risk assessment of MPs in lagoon sediment in this study, the risk was categorized as high for the polymer hazard index. The ecological risk index found Cd and As to have high ecological risk. High EF values were observed for As and Cd, which indicated severe enrichment. Based on the Igeo calculation, the majority of sampling stations were unpolluted to moderately contaminated ( Pb, Zn, Mg, and Co). Furthermore, there was no significant correlation between MPs and heavy metals, except for Zn (r = 0.697) and Cu (r = 0.61) (both p < 0.05). The results of this study might provide valuable data to develop conservation policies for coastal lagoon areas.